ANALYSIS OF PRODUCT ASSESSMENT RELATIONSHIP TO E-COMMERCE PRODUCT PURCHASE INTEREST SANJAI 3 SAUDARA - Putra, Andi; Budiarni, Rini; Putri, Nofelia (PT ANTIS International Publisher, 2024)
E-commerce has become a major platform for online transactions, where product ratings by customers serve as an indicator of quality and trust. This research aims to develop a web-based e-commerce application for Sanjai 3 Saudara and explore the impact of product ratings on online purchase interest. The application was developed using the Waterfall method, PHP, and the CodeIgniter Framework. The relationship between product ratings and purchase interest for the two best-selling products was analyzed using the Product Moment Correlation technique. To analyze the relationship between product assessment and e-commerce product purchase interest, you can break down the study into several key areas. The results showed a positive correlation between product ratings and online purchase interest, with a correlation coefficient of 0.703 for Sanjai Balado Bulat and 0.603 for Rendang Telur, indicating a strong correlation category. This approach will help provide a comprehensive analysis of how product assessments affect e-commerce purchase interest and offer actionable insights for improvement